Pengujian Kadar Air Biji Kakao (Theobroma cacao L .) dengan Suhu Tinggi dan Rendah Terhadap Kualitas Biji Kakao - Porsiana, Jefinta; Lesilolo, Marthini K; Riry, Johan (Fakultas Pertanian, Universitas Pattimura, 2024)
This study aims to compare the methods of testing the moisture reduction of cocoa beans with the high-temperature and low-temperature oven methods. The method used in this study was a comparative test between three cocoa clones and two moisture content test methods, namely using a low-temperature oven and a high-temperature oven. This research is experimental using a completely randomized design (CRD). The results of the cocoa moisture content test showed that each treatment of K2O2 and K1O2 was not significantly different from the results of the moisture content of cocoa beans. In contrast, the comparison of each treatment of K2O2, K1O2 and K3O2 was significantly different from the results of the moisture content of cocoa. Furthermore, for the K3O2 treatment compared to each of the K1O1, K2O1, and K3O1 treatments, the results of cocoa content were significantly different. For each treatment, K1O1, K2O1, and K3O1 did not differ significantly in the results of the moisture content of cocoa. High temperatures and low temperatures in Table 2 show that the K1O1 yield is 8.03%, significantly different from the K1O2 cocoa bean moisture content, which is 9.59%. and K3O1 7.57% with K3O2 which is 8.85 Testing the moisture content of cocoa seeds using the high-temperature oven method for 2 hours was significantly different from the low-temperature oven method for 17 hours. The proper method for testing the moisture content of cocoa beans is high temperature for 2 hours.